The Impact of Digital Transformation on Organizational Resilience in Nepalese SMEs: The Mediating Role of Entrepreneurial Orientation - Bhatt, Siddha Raj (Journal of Business and Management, 2025)
Background: Nepal’s economy depends heavily on small and medium enterprises (SMEs), although they confront obstacles like scare resources and external disruptions. Digital Transformation (DT) has emerged as a key strategy to enhance organizational resilience (OR), enabling the enterprises to adapt and recover from such challenges. However, the adoption of digital technology in Nepalese SMEs remains low and the relationship between DT, OR and EO (Entrepreneurial orientation) is underexplored. Objectives: This study investigates the impact of DT on OR in Nepalese SMEs, focusing on the mediating role of EO, to provide insights for building resilience and ensuring long-term sustainability in a dynamic business environment of Nepal. Methods: This study employs a quantitative research approach using a cross-sectional survey design. A non-probability convenience sampling method was used. Data were collected from 303 SME owners, managers, and employees of Kathmandu Valley. The variable responses were analyzed using descriptive statistics, Partial Least Squares Structural Equation Modeling (PLS-SEM) including bootstrapping, reliability and validity tests. The data were analyzed using R 4.4.1 version. Results: The study found that DT significantly improves OR in Nepalese SMEs by helping them adapt to challenges. While EO did not show a direct significant impact on OR, suggesting that proactiveness, innovativeness and risk-taking alone may not directly enhance OR, EO partially mediated the DT-OR relationship. Conclusion: DT enhances OR among Nepalese SMEs, by helping them to adapt to disruptions for sustainable growth. SMEs using digital technologies better handle market uncertainties. Although, EO alone does not directly impact OR, it partially mediates the DTOR relationship, meaning a strong entrepreneurial mindset helps SMEs fully leverage DT benefits. This highlights the importance of combining digital adoption with entrepreneurial culture to boost resilience and competitiveness. JEL Classification: L26, O33, M10